PENGARUH PERTUMBUHAN EKONOMI, PENGGUNAAN ENERGI DAN EKSPOR TERHADAP KUALITAS LINGKUNGAN DI INDONESIA - Putriani Putriani; Idris Idris; Melti Roza Adry (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2018)
This study aims to determine the Influence of Economic Growth, Energy Use and Export to Environmental Quality in Indonesia. The method used is Errror Correction Model (ECM) method. The data used are time series from 1983-2016 collected through documentation from BP Statistical World Energy website, World Bank, Indonesian Central Bureau of Statistics. The results of this study show that in the short term economic growth in linear effect negatively and not significant while the quadratic bepengaruh positive and insignificant to environmental quality in Indonesia. In the long run economic growth in linear has a negative and significant influence while the quadratic bepengaruh positive and significant to the kuaitas environment. Long-term and short-term energy use has a negative and significant impact on environmental quality in Indonesia. Exports in the long run have a negative and significant influence, while short-term has a negative and insignificant effect on environmental quality. The results of this study provide information about the quality of the environment so that the government and the community can protect, supervise and improve the quality of the environment in Indonesia.